PALEOGEOGRAPHICAL CONDITIONS OF ACCUMULATION OF OIL SHALE OF TITONIAN AGE IN THE CASPIAN SEDIMENTARY BASIN - E.S. Mussina; E.M. Fazylov (Reviews of Modern Science, 2023)
. In the Caspian sedimentary basin, four deposits of the Titonian age and several oil shale occurrences are developed richly. Regionally, the identified deposits belong to the Volga shale basin, most of which is located in Russia. Forecast resources in the northern part of the Kazakhstan side of the basin (Ozinkov, West Shagan, Barbastau, Novosemenov, Irtep perspective areas) amount to more than 13 bln tons of oil shale. But this is only a small part of the Caspian basin area. Shale oil is exposed in arc parts of salt domes. Most of their formations are overlaid by a case of younger rocks, which sink in all directions from the domes. In some places, the depth of the upper Jurassic strata reaches 1-1.5 km. The probability of detecting of new deep shale formations is high. Paleogeographical conditions of oil shale strata accumulation are restored. They were accumulating in depressions, which complicated the relief of the shallow platform sea bottom. The sea was warm, and the shallow depths provided good illumination of photic zones ensuring high bioproductivity of the sedimentation basin. Depressions created stagnant conditions, where clay and organic matter accumulated together. Oxygen-free stagnant conditions contributed to the conversion of the organic matter into kerogen. Such paleogeographical conditions existed in the entire water area of the Kazakhstan part of the upper Jurassic sea. It is necessary to carry out the specialized geological and geophysical works for a more accurate assessment of the resource potentials of the whole Caspian sea region.